THE GYM TEACHER IN VIEW OF THE GENERAL PUBLIC EDUCATION NETWORK OF JUIZ DE FORA / MG (Fiep Bulletin - online, 2012)
According to research conducted during the twentieth century and early nineteenth century, we see the dominance of sports in physical education classes, and a devaluation of gymnastics in the school, especially the General Gymnastics, or Gymnastics for All. The purpose of this study was to identify the vision and understanding of the content of physical education and sport gymnastics, to understand the place of General Gymnastics in schools. We conducted a questionnaire to teachers of public schools in the city of Juiz de Fora - Minas Gerais.
Keywords: Physical Education; Gymnastics; General Gymnastics